Implementasi Model Sorogan-Bandongan untuk Meningkatkan Keterampilan Berpikir Kritis pada Materi Asam Basa - Mar’atus Revana Sakti; Rinaningsih (PendIPA Journal of Science Education, 2026)
Critical thinking skills are an essential competency that needs to be developed in chemistry learning; however, conventional methods are considered suboptimal in facilitating the achievement of this competency. The Sorogan-Bandongan learning model, rooted in the pesantren tradition, emerges as an innovative alternative that synergistically integrates individual and classical approaches. This study aims to analyze the effectiveness of the Sorogan-Bandongan model in improving students' critical thinking skills on acid-base material compared to conventional learning. The study employed a quantitative approach with a quasi-experimental design, in which critical thinking skills were measured through four indicators: interpretation, analysis, inference, and explanation. The implementation of the model was assessed through observations across all meetings, yielding an average mode of ≥ 4, indicating that the model was carried out very well. The improvement of critical thinking skills in the class using the Sorogan-Bandongan model was higher than in the class using conventional methods, supported by the N-Gain Scores of the experimental class: interpretation indicator at 0.90, analysis indicator at 0.94, inference indicator at 0.89, and explanation indicator at 0.73. Meanwhile, the control class N-Gain Scores were: interpretation indicator at 0.69, analysis indicator at 0.60, inference indicator at 0.62, and explanation indicator at 0.72. The application of the Sorogan-Bandongan model is considered to facilitate students' understanding of acid-base material and enhance their active participation in learning. Therefore, it can be concluded that the Sorogan-Bandongan model is more effective as an innovative alternative compared to conventional methods for improving critical thinking skills in chemistry learning, particularly on the topic of acid-base.